Acta del Senado de Puerto Rico - Todd, Roberto H.; Barceló, Antonio R. (My University, 1921)
Discusiones en torno al "status" político de la isla.
Keywords: Self-determination, National--Puerto Rico.; Puerto Rico--Política y gobierno.; Puerto Rico--Politics and government.; Cuevas Zequeira, Sergio, 1863-1926; García Ducós, Juan; Tous Soto, José, 1874-1933; Barbosa, José Celso, 1857-1921; Martínez Nadal, Rafael, 1877-1941; Autodeterminación, Nacional--Puerto Rico.